Pentingnya Laporan Keuangan untuk Menilai Kinerja Suatu Perusahaan - Dharma, Budi; Ramadhani, Yus; Reitandi, Reitandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Performance is measured through the adequacy of capital, liquidity, and profitability indexes, which together provide an overview of the financial condition of the organization over a certain period of time, including the aspect of fund raising reflected in the capital indicator. The benefits of performance assessment for management include managing the organization's operations, assisting in decision-making, identifying the need for employee training and development, providing feedback to employees on how their superiors view their performance, and providing a basis for reward distribution. The purpose of this research is to determine the value of financial reporting in evaluating business performance. This research is beneficial for businesses because it provides information on the importance of financial reporting in evaluating company performance and making future decisions. Researchers can study the importance of financial reporting to assess the success of this research. This research uses a naturalistic approach, also known as a qualitative approach, using qualitative data or information consisting of words, sentences, diagrams, and pictures. Research data comes from secondary sources, such as documents, existing books, and literature studies.